2012
DOI: 10.1161/strokeaha.111.623033
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prediction of Poor Outcome After Thrombolysis Using Conservative Definitions of Symptomatic Hemorrhage

Abstract: Background and Purpose-Direct comparison of symptomatic intracerebral hemorrhage (sICH) rates among different thrombolysis studies is complicated by the variability of definitions of sICH. The prediction of outcome still remains unclear. Methods-Baseline data and clinical courses of patients treated with thrombolytic therapy were collected in a prospective database. The 3-month outcome was evaluated using the modified Rankin Scale. Results of 24-hour follow-up imaging were reevaluated by at least 2 independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 13 publications
2
46
1
1
Order By: Relevance
“…Studies showed that the ECASS II definition had the highest inter-rater agreement and the largest contribution to worst outcomes. 3,28 Patients with SICH per SITS-MOST was also found to have the highest risk for death and poor outcome. 28 A proportion of our patients were treated with a lower dose of intravenous tPA.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies showed that the ECASS II definition had the highest inter-rater agreement and the largest contribution to worst outcomes. 3,28 Patients with SICH per SITS-MOST was also found to have the highest risk for death and poor outcome. 28 A proportion of our patients were treated with a lower dose of intravenous tPA.…”
Section: Discussionmentioning
confidence: 92%
“…3,28 Patients with SICH per SITS-MOST was also found to have the highest risk for death and poor outcome. 28 A proportion of our patients were treated with a lower dose of intravenous tPA. Whether the incidence of SICH is similar between standard dose and low-dose regimens remains unclear.…”
Section: Discussionmentioning
confidence: 92%
“…The definition of sICH according to ECASS II was chosen because it combines high inter-rater agreement 25 with high predictive value for the worst outcome after thrombolysis. 26 However, we also assessed the occurrence of sICH according to SITS definition (ie, local or remote parenchymal hemorrhage type 2 combined with NIHSS score worsening of at least 4 points or leading to death within 22-36 hours).…”
Section: Methodsmentioning
confidence: 99%
“…5 For the purpose of multivariable analysis, we have chosen the ECASS II definition of sICH because it combines high interrater agreement 12 with high predictive value for the worst outcome after thrombolysis.…”
Section: Methodsmentioning
confidence: 99%